The effect of the shape of gold core-mesoporous silica shell nanoparticles on the cellular behavior and tumor spheroid penetration - Dias, Diana Rodrigues (2018)
Size, surface charge, and shape have a huge influence on the behavior, cellular uptake, and cytotoxic profile of nanoparticles. Herein, gold core and silica shell based nanoparticles (Au–MSSs) with spherical or rod-like shape were produced, in order to disclose the effect of the shape of nanomaterials on the cellular uptake, reactive oxygen species (ROS) production, 3D tumor spheroid penetration and cytotoxicity towards cancer cells. The Au–MSS spheres induced greater reduction of the ROS content of cancer cells and also displayed a more homogeneous distribution and penetration in 3D tumor spheroids. However, the Au–MSS rods show enhanced cellular migration and uptake in 2D cell cultures, which results in a higher drug delivering capacity. Furthermore, the Au–MSS rods displayed an enhanced cellular cytotoxicity upon laser irradiation (808 nm, 1.7 W cm−2, 10 min), where less than 10% of cells remained viable. In addition, both Au–MSSs have the potential to be used as imaging agents, which further expands their applicability as theranostic agents in the biomedical area. In summary, the obtained results show that the shape of Au–MSSs is crucial for their biological performance, which will have a great influence on their therapeutic outcome. Therefore, our findings may provide useful information for the development and design of new drug delivery systems towards a more effective therapy.